Physical activity, gestational weight gain in obese patients with early gestational diabetes and the perinatal outcome - a randomised-controlled trial - Lukasz Adamczak; Urszula Mantaj; Rafał Sibiak; Paweł Gutaj; Ewa Wender-Ozegowska (BMC, 2024)
Abstract Background Excessive gestational weight gain, especially among women with gestational diabetes, is associated with several adverse perinatal outcomes. Our study aimed to analyse the impact of the use of pedometers to supervise physical activity on maternal health and the obstetric outcomes of pregnant women with obesity and early gestational diabetes. Methods 124 pregnant patients were enrolled in the presented research. Inclusion criteria: singleton pregnancy, age > 18 years, gestational diabetes diagnosed in the first half of pregnancy (< 20th week of pregnancy), obesity according to the American Endocrine Society criteria. Each patient was advised to take at least 5000 steps daily. Patients were randomly assigned to pedometers (N = 62), and were recommended to monitor daily the number of steps. The group without pedometers (N = 62) was not observed. Visit (V1) was scheduled between the 28th and 32nd gestational week (GW), and visit (V2) occurred between the 37th and 39th GW. Anthropometric measurements and blood samples were collected from all patients at each appointment. Foetal and maternal outcomes were analysed at the end of the study. Results In the group supervised by pedometers, there were significantly fewer newborns with macrosomia (p = 0,03). Only 45% of patients satisfied the recommended physical activity guidelines. Patients who walked more than 5000 steps per day had significantly higher body weight at baseline (p = 0,005), but weight gain was significantly lower than in the group that did not exceed 5000 steps per day (p < 0,001). The perinatal outcome in the group of patients performing more than 5000 steps did not demonstrate significant differences with when compared to less active group. ROC curve for weight gain above the guidelines indicated a statistically substantial cut-off point for this group at the level of 4210 steps/day (p = 0.00001). Conclusions Monitoring the activity of pregnant patients with gestational diabetes and obesity by pedometers did not have a significantly impact on their metabolic control and weight gain. However, it contributed to less macrosomia. Furthermore, physical activity over 5,000 steps per day positively affects weight loss, as well as contributes to improved obstetric and neonatal outcomes.